Competency in chest X-ray interpretation: Variations across medical experiences and training levels - Koa, Ai Jiun; Cheah, Whye Lian; Yew, Ting Ting; Ahmad Tirmizi, Jobli (Malaysian Medical Association, 2026)
ABSTRACT Introduction: Chest X-ray (CXR) remains one of the most commonly used diagnostic imaging tools in clinical practice. However, the accuracy and competency in reading and interpreting CXRs can vary significantly across different levels of medical practitioners, ranging from house officers to senior specialists. The purpose of this study was to assess competency in CXR interpretation among doctors at different stages of their medical careers. Material and Methods: This is a cross-sectional study conducted using CXRs, which were displayed digitally. A total of 305 participants were recruited, including house officers, medical officers, and registrars in specialty training. A standard set of ten radiographs was chosen, and the participants were required to interpret the CXR in multiple-choice format. Data analysis was performed via IBM SPSS Statistics software, version 25. Results: Clinical history improved the ability to accurately interpret CXR, with the percentage of participants who accurately interpreted CXRs increasing from 21% of participants who achieved high scores without clinical history to 63.6% of participants who achieved high scores with clinical history. The participants' field of interest and confidence level when reporting a CXR without history were associated with higher accuracy (p<0.05) when interpreting a CXR. However, when the clinical history was given to the participant, only the confidence level of the participant affected the final score of the CXR. There is no significant difference in the ability of doctors to interpret CXR despite the difference in seniority in practice; moreover, undergraduate exposure does not play a significant role. Conclusion: Structured teaching, continuous practice, feedback and integration into clinical decision-making are the keys that translate to greater competency in CXR interpretation. Future researches should emphasize on multicenter approach as it enhances the generalizability of findings to a broader national context.